2017
DOI: 10.1007/s10126-017-9764-6
|View full text |Cite
|
Sign up to set email alerts
|

Chimeras Linked to Tandem Repeats and Transposable Elements in Tetraploid Hybrid Fish

Abstract: The formation of the allotetraploid hybrid lineage (4nAT) encompasses both distant hybridization and polyploidization processes. The allotetraploid offspring have two sets of sub-genomes inherited from both parental species, and therefore, it is important to explore its genetic structure. Herein, we construct a bacterial artificial chromosome library of allotetraploids, and then sequence and analyze the full-length sequences of 19 bacterial artificial chromosomes. Sixty-eight DNA chimeras are identified, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Furthermore, replication slippage, or the imprecise cutting of an unpaired duplication during large-loop mismatch repair, may represent additional mechanisms for the formation of chimeric genes (Rogers et al, 2009). In addition, double-strand break (DSB) is more likely to occur at tandem repeats locus during the process of DNA replication, thus, a chimera is formed by recombination between different sequences during the process of DSB repair (Ye et al, 2017) However, the causative mechanism(s) involved could not be identified by our present analyses.…”
Section: Potential Mechanisms Related To Chimeric Genesmentioning
confidence: 99%
“…Furthermore, replication slippage, or the imprecise cutting of an unpaired duplication during large-loop mismatch repair, may represent additional mechanisms for the formation of chimeric genes (Rogers et al, 2009). In addition, double-strand break (DSB) is more likely to occur at tandem repeats locus during the process of DNA replication, thus, a chimera is formed by recombination between different sequences during the process of DSB repair (Ye et al, 2017) However, the causative mechanism(s) involved could not be identified by our present analyses.…”
Section: Potential Mechanisms Related To Chimeric Genesmentioning
confidence: 99%
“…4nAT has two sets of genomes from RCC and two sets of genomes from CC, the stability of which is directly related to the stability of tetraploid germplasm. Previous studies have demonstrated stable heterozygosity by comparing genetic polymorphisms (Li, Liu, Zhang, Lu, & Liu, 2005; Li et al, 2003), mitochondrial genome analysis (Guo, Liu, Yan, & Liu, 2004), BAC library construction (Ye et al, 2017a; Wang et al, 2015), transcriptome and genome sequencing (Liu et al, 2016; Ren et al, 2019), fluorescence in‐situ hybridization (FISH) of somatic chromosomes (Zhang et al, 2015), and so on. However, whether the occurrence of meiotic homologous chromosomes pair between identical chromosomes or between heterologous chromosomes remains unclear, which is directly related to the stability of genetic germplasm in diploid gametes.…”
Section: Introductionmentioning
confidence: 99%